VIBRATION SIGNAL ANALYSIS FOR CAVE DETECTION AS BASIC OF DEVELOPING PUMP OPERATIONS: CASE STUDY UNIT DISTILLATION PLN BELAWAN - Muhammad Zukhri Lubis; Ikhwansyah Isranuri (JOURNAL OF SCIENCE AND APPLIED ENGINEERING, 2018)
Cavitation occurs due to the formation of empty cavities in the fluid flow that decreases pressure quickly. When cavitation occurs then the pump performance will decrease marked with noise and when this condition is not addressed will cause damage to the pump components. The distillation pump working under vacuum pressure and working temperature at 38 ° C is susceptible to cavitation. The pressure and temperature conditions of this distillation pump work result in faster fluid evaporation and eventually trigger cavitation. To avoid the occurrence of cavitation, it must be known operational limits concerning the pressure and working capacity of the distillation pump. The operational limit of this pump is between the shut-off point meaning there is no flow and run-out point which means the full capacity of the pump. This study aims to determine the operating limits of safe distillation pumps both from pressure and capacity. The experimental methodology used is to vary the capacity of the pump by adjusting the opening valve discharge at 100%, 90%, 80% and 70% capacities. Then for each capacity varied also the suction pressure of pump at 0 mmHg, -7 mmHg, -15 mmHg and -22 mmHg by arranging vacuum pump. The magnitude of the vibration response is measured to determine the effect of the capacity and variation of pump suction pressure. With this method can be known range of capacity and pressure suction safe for operation of distillation pump. The results showed that the highest vibration value was in the axial direction. Vibration spectrum value spread over the range 1600 - 1900 Hz with the highest value is at 100% capacity (0.00278 m3 / sec) suction pressure -0 mmHg with amplitude of 0.410 g at 1660 Hz frequency. While the lowest vibration value is at a flow rate of 0.00208 m3 / sec with an amplitude of 0.210 g at a frequency of 1816 Hz. While the minimum flow rate to avoid the occurrence of cavitation due to recirculation flow is equal to 0.00172 m3 / sec. Keywords: cavitation, distillation pump, operational limit, valve discharge, vacuum pump